Care and Neurorehabilitation in the Disorder of Consciousness: A Model in Progress. (29th March 2015) - Dolce, Giuliano; Arcuri, Francesco; Carozzo, Simone; Cortese, Maria Daniela; Greco, Pierpaolo; Lucca, Lucia Francesca; Pignolo, Loris; Pugliese, Maria Elena; Riganello, Francesco
Abstract : The operational model and strategies developed at the Institute S. Anna-RAN to be applied in the care and neurorehabilitation of subjects with disorders of consciousness (DOC) are described. The institute units are sequentially organized to guarantee appropriate care and provide rehabilitation programs adapted to the patients' clinical condition and individual's needs at each phase of evolution during treatment in a fast turnover rate. Patients eligible of home care are monitored remotely. Transferring advanced technology to a stage of regular operation is the main mission. Responsiveness and the time windows characterized by better residual responsiveness are identified and the spontaneous/induced changes in the autonomic system functional state and biological parameters are monitored both in dedicated sessions and by means of an ambient intelligence platform acquiring large databases from traditional and innovative sensors and interfaced with knowledge management and knowledge discovery systems. Diagnosis of vegetative state/unresponsive wakefulness syndrome or minimal conscious state and early prognosis are in accordance with the current criteria. Over one thousand patients with DOC have been admitted and treated in the years 1998–2013. The model application has progressively shortened the time of hospitalization and reduced costs at unchanged quality of services.